2002
DOI: 10.1111/1467-646x.00077
|View full text |Cite
|
Sign up to set email alerts
|

Cultural Influences on Judgments of Professional Accountants in Auditor–Client Conflict Resolution

Abstract: This study examines cultural influences on professional judgments of Australian, Indian and Chinese Malaysian accountants in relation to auditor-client conflict resolution. The study draws on cultural characteristics of, and differences among, these societies to formulate hypotheses that Australian accountants are less likely to resolve audit conflicts by acceding to clients than Indian and Chinese Malaysian accountants, and are also less accepting of resolving audit conflicts in this way. Data are gathered th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(71 citation statements)
references
References 22 publications
2
66
0
2
Order By: Relevance
“…Using the Hofstede Power Distance and individualism dimensions, Patel et al (2002) reported differences in the responses of accountants from Chinese Malaysia (n ¼ 92), India (n ¼ 84), and Australia (n ¼ 72) on an auditor-client conflict scenario. The Australian accountants were less likely to resolve, and less accepting of resolving, auditorclient conflicts by acceding to clients.…”
Section: Linking Culture and Ethicsmentioning
confidence: 99%
“…Using the Hofstede Power Distance and individualism dimensions, Patel et al (2002) reported differences in the responses of accountants from Chinese Malaysia (n ¼ 92), India (n ¼ 84), and Australia (n ¼ 72) on an auditor-client conflict scenario. The Australian accountants were less likely to resolve, and less accepting of resolving, auditorclient conflicts by acceding to clients.…”
Section: Linking Culture and Ethicsmentioning
confidence: 99%
“…Potential evaluation of the effects of audit partner characteristics on audit quality may include analysis of partners signing the audit report and engagement tenure. Extant research suggests that cultural factors influence professional and auditor judgment (Hofstede 2001;Cohen, Pant, and Sharp 1995;Patel, Harrison, and McKinnon 2002;Hughes, Sander, Higgs, and Cullinan 2009;McGuire, Omer, and Sharp 2012;Knechel et al 2013).…”
Section: Audit Professionals (Inputs)mentioning
confidence: 99%
“…while the major criticisms levelled at Hofstede (2001) include his generalisations about national culture based upon an analysis of sub-national populations and his inferring of national culture from averaging situationally-specific opinions of culture (McSweeney, 2002), many studies have utilised Hofstede's (1994) VSM instrument to study inter-country comparative ethical attitudes, decision-making and business practices (Armstrong, 1996;McKinnon, 2002;Nyaw & Ng, 1994;Patel, Harrison & Sims, 2006;Sims & Gegez, 2004;Tsui, 1996;Tsui & windsor, 2001). Sondergaard (1994) reports that over 60 published replications using the VSM instrument largely confirm Hofstede's (1994) findings.…”
Section: National Culture and Ethicsmentioning
confidence: 99%